2019
DOI: 10.1111/1365-2656.13073
|View full text |Cite
|
Sign up to set email alerts
|

Specialization and niche overlap across spatial scales: Revealing ecological factors shaping species richness and coexistence in Australian songbirds

Abstract: Ecological specialization enables the partitioning of resources and thus can facilitate the coexistence of species and promote higher species richness. Specialization and niche partitioning are expected to exert a decisive influence on local spatial scales, while species richness at regional scales should be shaped mostly by historical factors and abiotic conditions. Moreover, specialization is expected to be particularly important in communities that are exceptionally species rich for their environmental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The foraging niche width was wider in the Spectacled Whitestart compared to the Slate-throated Whitestart, which is also consistent with differences in vegetation between the species as a relatively more diverse (less uniform) vegetation structure was detected in the territories of the Spectacled Whitestart than the Slate-throated Whitestart. The ecological niche overlap index based on foraging site location characteristics was in the range of values indicating lower/intermediate degree of niche overlap 57 confirming that the two species differ in their ecological niches. All these results combined with the lack of any observed aggression between the two species are consistent with the ecological sorting mechanism 6 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The foraging niche width was wider in the Spectacled Whitestart compared to the Slate-throated Whitestart, which is also consistent with differences in vegetation between the species as a relatively more diverse (less uniform) vegetation structure was detected in the territories of the Spectacled Whitestart than the Slate-throated Whitestart. The ecological niche overlap index based on foraging site location characteristics was in the range of values indicating lower/intermediate degree of niche overlap 57 confirming that the two species differ in their ecological niches. All these results combined with the lack of any observed aggression between the two species are consistent with the ecological sorting mechanism 6 .…”
Section: Discussionmentioning
confidence: 65%
“…Degree of overlap of resource utilization (foraging niches) between the two species was calculated according to Pianka 67 : where overlaps (O's) are symmetrical and p ij and p ik are the proportions of the ith resource (foraging places type) used by the jth and kth species. The index can range from 0 (no overlap) to 1 (full overlap), but in practice for similar avian foraging site distribution data the range of recorded values is approximately from ~ 0.2 to ~ 0.4 for low overlap and from ~ 0.6 to ~ 0.8 for high niche overlap 57 .…”
Section: Methodsmentioning
confidence: 99%
“…Our finding that trophic partitioning only occurs at the fine spatial scale is consistent with other studies of bats (Peixoto et al., 2018), ants (Albrecht & Gotelli, 2001), parasitoid insects (Harvey et al., 2014) and bobcats (Lewis et al., 2015), showing that interspecific interactions are more important for shaping community structure at fine rather than broad spatial scales. However, this pattern is not universal (e.g., Harmáčková et al., 2019). In our study system, these fine‐scale mechanisms could contribute to enabling broad‐scale range overlap across the north of the Iberian Peninsula because theoretical studies have shown that fine‐scale coexistence mechanisms can prevent competitive effects from scaling‐up and affecting the broad‐scale distributions of species (Godsoe et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the higher niche similarity may lead to a more clustered phylogenetic structure (Bennett et al, 2013; Mayfield & Levine, 2010). Likewise, the lower niche overlap intensity in the seriously degraded lands shows that niche differences may be necessary to promote species coexistence in resource‐constrained habitats (Godoy et al, 2014; Harmáčková et al, 2019; Kent et al, 2019). Importantly, the species had a lower species:family ratio and clear variation in phenotypic shapes (such as tall grasses and dwarf forbs) in the highly degraded lands.…”
Section: Discussionmentioning
confidence: 99%
“…We set an index that is higher than 0.5 as the high spatial overlap degree (R. H. Liu et al, 2018). It can thus be used to assess the potential for competition between species in a community (Harmáčková, Remešová, & Remeš, 2019). We also calculated the Shannon–Wiener niche breadth (Bi) (Colwell & Futuyma, 1971) and overlap (O ik ) (Bewick, Chisholm, Akcay, & Godsoe, 2015; Pianka, 1973) using the following equations: Bi=j=1r()PijlnPij Pij=truenitalicijNitalicij Oik=j=1rPijPkj()j=1rPij2()j=1rPkj2. …”
Section: Methodsmentioning
confidence: 99%